Reporting of IMMPACT-recommended core outcome domains among trials assessing opioids for chronic non-cancer pain. Issue 9 (September 2015) - Mulla, Sohail M.; Maqbool, Amna; Sivananthan, Laxsanaa; Lopes, Luciane C.; Schandelmaier, Stefan; Kamaleldin, Mostafa; Hsu, Sandy; Riva, John J.; Vandvik, Per Olav; Tsoi, Ludwig; Lam, Tommy; Ebrahim, Shanil; et al.
Abstract : Abstract: The Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) has recommended that trialists evaluating treatments for chronic pain should consider reporting 9 patient-important outcome domains. We examined the extent to which clinical trials evaluating the effect of opioids for chronic non-cancer pain (CNCP) report outcome domains recommended by IMMPACT. We systematically searched electronic databases for English-language studies that randomized patients with CNCP to receive an opioid or a non-opioid control. In duplicate and independently, reviewers established the eligibility of each identified study and recorded all reported outcome domains from eligible trials. We conducted a priori regression analyses to explore factors that may be associated with IMMPACT-recommended outcome domains. Among 156 eligible trials, reporting of IMMPACT-recommended outcome domains was highly variable, ranging from 99% for pain to 7% for interpersonal functioning. Recently published trials were more likely to report the effect of treatment on physical functioning, emotional functioning, role functioning, sleep and fatigue, and participant disposition. Trials for which the corresponding author was from North America were more likely to report treatment effects on physical functioning and participant ratings of improvement and satisfaction with treatment. Trials published in higher impact journals were more likely to report treatment effects on emotional function, but less likely to report participant ratings of improvement and satisfaction with treatment. Most IMMPACT domains showed an increased rate of reporting over time, although many patient-important outcome domains remained unreported by over half of all trials evaluating the effects of opioids for CNCP. Abstract : Supplemental Digital Content is Available in the Text.Among clinical trials of opioids for chronic non-cancer pain, reporting of 9 IMMPACT-recommended outcome domains ranged from 99% for pain to 7% for interpersonal functioning.